Pemberdayaan Remaja Putri dalam Pencegahan Anemia melalui Inovasi Puding Daun Katuk di SMPN 02 Lirung Kabupaten Kepulauan Talaud - Yulien Adam; Dian Pratiwi; Nana Maryana (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Anemia among adolescent girls remains a significant public health problem that affects physical development, cognitive performance, and academic productivity. Limited nutritional knowledge and the underutilization of locally available nutrient-rich foods contribute to the high prevalence of anemia in this population. This community service program aimed to improve students’ knowledge of anemia prevention through interactive nutrition education and a hands-on demonstration of katuk leaf pudding preparation, a local food rich in iron. The implementation consisted of participatory planning, educational lectures, cooking demonstrations, and evaluation of students’ knowledge using pre-test and post-test assessments involving 85 participants. Data were analyzed through descriptive statistics, normality testing, and paired t-test. The results showed a significant improvement in students’ knowledge after the intervention. The mean knowledge score increased from 9.81 in the pre-test to 15.62 in the post-test. These findings demonstrate that practical, hands-on nutrition education through katuk leaf pudding preparation is highly effective in enhancing students’ understanding of anemia prevention and in promoting the use of local nutritious foods within the school community.